De novo donor‐specific anti‐HLA antibodies mediated rejection in liver‐transplant patients. (December 2015) - Del Bello, Arnaud; Congy‐Jolivet, Nicolas; Danjoux, Marie; Muscari, Fabrice; Lavayssière, Laurence; Esposito, Laure; Cardeau‐Desangles, Isabelle; Guitard, Joëlle; Dörr, Gaëlle; Milongo, David; Suc, Bertrand; Duffas, Jean Pierre; et al.
Summary: The incidence and consequences of de novo donor‐specific anti‐HLA antibodies (DSAs) after liver transplantation (LT) are not well known. We investigated the incidence, risk factors, and complications associated with de novo DSAs in this setting. A total of 152 de novo liver‐transplant patients, without preformed anti‐HLA DSAs, were tested for anti‐HLA antibodies, with single‐antigen bead technology, before, at transplantation, at 1, 3, 6 and 12 months after transplantation, and thereafter annually and at each time they presented with increased liver‐enzyme levels until the last follow‐up, that is, 34 (1.5–77) months. Twenty‐one patients (14%) developed de novo DSAs. Of these, five patients had C1q‐binding DSAs (24%). Younger age, low exposure to calcineurin inhibitors, and noncompliance were predictive factors for de novo DSA formation. Nine of the 21 patients (43%) with de novo DSAs experienced an acute antibody‐mediated rejection (AMR). Positive C4d staining was more frequently observed in liver biopsies of patients with AMR (9/9 vs. 1/12, P  <   0.0001). Eight patients received a B‐cell targeting therapy, and one patient received polyclonal antibodies. Only one patient required retransplantation. Patient‐ and graft‐survival rates did not differ between patients with and without DSAs. In conclusion, liver‐transplant patients with liver abnormalities should be screened for DSAs and AMR.